Scientific and Pedagogical Continuity of al-Farabi and Abai - Балықбаев, Такир; Бидайбеков, Есен (Pedagogy and Psychology, 2020)
The paper considers the continuity of the heritage of Al-Farabi and Abai. The authors of the paper highlight the issues of continuity, connectivity, rootedness of two arys, mainly scientific and pedagogical, as well as religious and philosophical, musical, poetic, historical and ethnographic content. The article emphasizes that A. Kubessov considered the general pedagogical ideas of Abai and Al-Farabi, upbringing and edification, issues of education in the pedagogical system, complementing each other, inseparably, in dialectical unity and uniting them with the human community, he determined their scientific and pedagogical continuity. Also, attention is paid to the importance of research as a deep and reasonable preconditions for conducting pedagogical and didactic research in the disciplines «Poetic irony», «Thoughts on music», «Genre similarities in the work of Al-Farabi and Abai», «Religious and philosophical roots», «Views on Turkic history and ethnography», close to the field of scientific and pedagogical continuity, which are part of the continuity of the heritage of Al-Farabi and Abai.